An Analysis of Consumer Trust During Online Purchasing Decision Process in Cross-Cultural Perspective: A Case Study of Online Marketplace - Adyatma, Prastha; Tarunajaya, Wisnu Bawa (Formosa Journal of Multidisciplinary Research, 2024)
The purpose of this research study is to analyse consumer trust during the online purchasing decision process from a cross-cultural perspective, specifically in the case of an online marketplace. The study has three primary objectives: to explore the value and importance of online purchasing among customers in different cultures, to examine the factors that influence consumers in different cultures to gain trust in online purchasing, and to assess the factors that affect consumer trust in different cultures when purchasing goods online. The study will use focus group discussions to gather data from participants in Indonesia and China, and thematic analysis will be conducted to analyse the gathered data. The findings of this study will be significant in providing insights into the factors that influence consumer trust in online purchasing decisions, specifically in cross-cultural contexts. Understanding these factors can help online marketplaces improve their services and increase consumer trust, which can lead to increased revenue and customer loyalty. Moreover, the study will contribute to the body of knowledge in the field of cross-cultural marketing, as it will provide insights into how cultural factors influence consumer behaviour in online marketplaces.